What Research in Science Education is Needed to Strengthen the College Science Program? - Branson, Herman (Science Education, 1956)
The article focuses on the research in science education needed to strengthen the college science program in the U.S. According to the author, science education on the college level is large with a limit time in providing solutions to problems. The author cited several problem areas in the college level in view of the present needs, including the lecture procedure in classes, recitations and problems sessions and choice of experiments during laboratory. From an informal survey among college teachers regarding their choice on how should the students work, it revealed a majority choice for students to be working in pairs.